Digital Storytelling and STEM Identity: A Narrative Inquiry of Female High School Students in Japan - Kaito Tanaka; Riko Kobayashi; Haruka Sato (Yayasan Adra Karima Hubbi, 2025)
Background. Despite Japan’s global reputation for technological innovation, female representation in science, technology, engineering, and mathematics (STEM) fields remains disproportionately low. Cultural expectations, gender norms, and limited role models contribute to the underrepresentation of young women in STEM pathways. Purpose. This study explores how digital storytelling can serve as a transformative pedagogical tool to support the development of STEM identity among female high school students in Japan. Method. Using a qualitative narrative inquiry approach, the study engaged 15 female students aged 16–18 from three urban high schools. Participants created and reflected on personal digital stories that connected their lived experiences with STEM-related aspirations, interests, or challenges. Results. Data were collected through digital artifacts, in-depth interviews, and reflective journals, then analyzed thematically. Findings reveal that digital storytelling enabled participants to articulate their evolving sense of agency, challenge internalized gender stereotypes, and envision themselves in future STEM careers. The process fostered increased confidence, self-recognition as potential STEM contributors, and a sense of belonging in scientific discourse. Conclusion. This study demonstrates the potential of narrative-based, multimodal learning tools in reshaping STEM identity formation for underrepresented groups. It contributes to feminist pedagogy and STEM education research through the intersection of narrative, identity, and digital media.